THE INFLUENCE OF BRAND IMAGE, PRICE, AND PRODUCT QUALITY ON PURCHASE DECISIONS (Empirical Study on Students of SMK Muhammadiyah 5 Kisaran) - Durahman Marpaung; Bakti Bakti; Liza Saragih (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The purpose of the study was to analyze the effect of Brand Image, Price and Product Quality on Consumer Purchase Decisions on OPPO Smartphones, especially Students of SMK Muhammadiyah 5 Kisaran. The method used is descriptive associative with a quantitative approach. The sample used in this study amounted to 90 respondents consisting of students of SMK Muhammadiyah 5 Kisaran. The results show that Brand Image, Price and Product Quality on Purchase Decisions simultaneously have a significant effect on purchasing decisions, but partially only product quality has no significant effect on purchasing decisions..